First report of sugarcane mosaic virus in achira (Canna edulis Ker.) in Nariño, Colombia - Betancourt, Carlos; Salomón, Carlos; Montaño, Santiago; Salazar, Claudia; Uribe, Pedro; Martínez, Angélica; Muñoz, Lucely; Cuervo Ibáñez, Maritza (Universidad de Ciencias Aplicadas Y Ambientales - UDCA, 2020)
Achira (Canna edulis Ker.) is a cultivated species for handcrafted food products and starch production. In Colombia is estimated an achira cultivated area of 800 ha; in the department of Nariño there has been a disturbance of viral etiology, known by farmers as Streak Virus, due to its symptoms in the leaves, but without previous records in the area. The disease causes losses in performance, although they have not been established precisely. In order to clarify the nature of this pathology and the identity of the pathogen associated with the problem, an investigation was carried out at the University of Nariño, by means of molecular tests of PCR and RT-PCR, sequencing, serology and electron microscopy, of foliar samples collected in the producing areas. The most outstanding symptoms in affected tissues were yellow mosaic, mottled, chlorotic streak and ribs discoloration, among others. There were no cytoplasmic inclusions similar to those produced by Potyvirus, nor viral particles were observed, nor serology positive results, but it was possible to achieve the amplifi cation of a cDNA fragment, with specific primers for Potyvirus and 98% of homology of the sequences with Sugarcane mosaic virus. This is the first SCMV report in achira in Nariño, Colombia.